2020
DOI: 10.1088/2515-7647/aba670
|View full text |Cite
|
Sign up to set email alerts
|

Spike-based information encoding in vertical cavity surface emitting lasers for neuromorphic photonic systems

Abstract: The ongoing growth of use-cases for artificial neural networks (ANNs) fuels the search for new, tailor-made ANN-optimized hardware. Neuromorphic (brain-like) computers are among the proposed highly promising solutions, with optical neuromorphic realizations recently receiving increasing research interest. Among these, photonic neuronal models based on vertical cavity surface emitting lasers (VCSELs) stand out due to their favourable properties, fast operation and mature technology. In this work, we experimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 64 publications
0
29
0
Order By: Relevance
“…Josephson junctions [10], micropillar lasers [24], excitable semiconductor lasers, including a graphene laser with saturable absorber [25], quantum-dot laser [26][27][28], microring resonators [29], vertical cavity surface emitting lasers (VCSELs) [30][31][32] and multi-section VCSELs with saturable absorber [33,34]. Table I (PDC) [36] as shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Josephson junctions [10], micropillar lasers [24], excitable semiconductor lasers, including a graphene laser with saturable absorber [25], quantum-dot laser [26][27][28], microring resonators [29], vertical cavity surface emitting lasers (VCSELs) [30][31][32] and multi-section VCSELs with saturable absorber [33,34]. Table I (PDC) [36] as shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Without any specific control, giant pulses are expected to pop up randomly and may not be reliable for applications. Yet, extensive studies about controllable giant pulses can be found in the literature [113][114][115][116] with the view of taking advantage of these sudden bursts for high precision remote-sensing [117] or photonic reservoir computing [118].…”
Section: Giant Pulses In Opticsmentioning
confidence: 99%
“…high speed, ease to integrate in 2D arrays, low energy operation, high coupling efficiency to optical fibres, etc.). A number of neuronal functionalities have been recently demonstrated in VCSELs, including ultrafast spike activation and inhibition 32 , networked spiking communication 33 , spike rate encoding 34 and pattern recognition 35 , to name a few. Furthermore, theoretical spin flip model (SFM) studies 36 indicate that VCSELs have the potential to present a pathway to unsupervised learning, via the neuron-inspired spike-timing dependent plasticity (STDP) technique.…”
Section: Introductionmentioning
confidence: 99%